The Responsibility for Peace (R4P): Understanding the study of peace from a global justice and development perspective. - Tacheva, Blagovesta; Brown, Garrett Wallace; Bohm, Alexandra (Rivista Italiana di Filosofia Politica, 2024)
This article introduces a new conceptualisation of the relationship between global distributive justice, development, and the study of peace, which we label the Responsibility for Peace (R4P). In doing so, the article examines the notion of positive peace within peace studies, its relation to arguments within global distributive justice, and to what degree this important relationship is recognised in the primary international framework to prevent and protect populations from mass atrocity crimes, the Responsibility to Protect (R2P). The article argues that despite growing recognition about the links between peace and development within both R2P and global justice discussions, it remains insufficient in terms of positive peace, thus requiring a new heuristic. In response, we argue that global justice demands refocused moral commitments to jus ante bellum (establishing global justice before war) and that this necessitates greater focus on the study of positive peace mechanisms, the identification and reform of structural injustices (against structural violence), and a retooled emphasis on human-centred development that can transcend existing legacies. In other words, we need to better focus on causes and not symptoms. It is this triangulation that we label the Responsibility for Peace (R4P), which should operate both prior to, and independently of, the Responsibility to Protect (R2P).